the equation of a line is given by Ax + By = C. Solve for y. A. y = C - Ax B. y=C/B -Ax/B C. y = B (C - Ax) D. y = C - Ax/B

1 answer

To solve for \( y \) in the equation of the line given by \( Ax + By = C \), we need to isolate \( y \).

Starting with the equation:

\[ Ax + By = C \]

  1. Subtract \( Ax \) from both sides:

\[ By = C - Ax \]

  1. Now, divide both sides by \( B \) to solve for \( y \):

\[ y = \frac{C - Ax}{B} \]

This simplifies to:

\[ y = \frac{C}{B} - \frac{A}{B}x \]

Among the answer choices provided, the one that matches our derived equation is:

B. \( y = \frac{C}{B} - \frac{A}{B}x \).

So the correct answer is B.